Major Abdominal Surgery in Nursing Home Residents: A National Study - Finlayson, Emily (Ann Surg, 2011)
OBJECTIVE: To determine surgical risk in nursing home residents undergoing major abdominal surgery. SUMMARY BACKGROUND DATA: Recent studies suggest that surgery can be performed safely in the very old. Surgical risk in nursing home residents is poorly understood. METHODS: We used national Medicare claims and the nursing home Minimum Data Set (1999–2006) to identify nursing home residents undergoing surgery (surgery for bleeding duodenal ulcer, cholecystectomy, appendectomy, and colectomy, n=70,719). We compared operative mortality and use of invasive interventions (mechanical ventilation, intravascular hemodynamic monitoring, feeding tube placement, tracheostomy, and vena cava filters) among nursing home residents to rates among non-institutionalized Medicare enrollees age 65 and older undergoing the same procedures. (n=1,060,389). We adjusted for patient characteristics using logistic regression. RESULTS: Operative mortality among nursing home residents was substantially higher than among non-institutionalized Medicare enrollees for all procedures (surgery for bleeding duodenal ulcer, 42% v. 26%, adjusted odds ratio (AOR) 1.79; colectomy, 32% v. 13%, AOR 2.06; appendectomy, 12% v. 2%, AOR 3.27; cholecystectomy, 11% v. 3%, AOR 2.65; p<0.001 for all comparisons). Overall, invasive interventions were more common among nursing home residents than controls (ranging from 18% and 5%, respectively, for cholecystectomy to 55% and 43%, respectively, for surgery for bleeding duodenal ulcer, p<0.0001 for all comparisons). CONCLUSIONS: Nursing home residents experience substantially higher rates of mortality and invasive interventions after major surgery than other Medicare beneficiaries that are independent of age and measured comorbidities. Our data suggest that the risks of major surgery are substantially higher in nursing home residents and this information should inform decisions of physicians and patients and their families.